Petro-physical Analysis of the Mushrif Formation Units in the Nasiriyah Field, Southern Iraq - Ali Kareem Jaheed (University of Thi-Qar Journal of Science, 2025)
Mushrif Formation is one of the major geological formations in southern Iraq because of its petro-physical characteristics and geographical extensions, which makes it an excellent oil reserve in that region. The present investigation identified the petro-physical characteristics of the Nasiriyah Oilfield's Mushrif Formation by interpreting the geophysical data of three wells (NS-1, NS-3, and NS-5).This study was carried out by the software (Techlog software 15.3). The study relied on quantitative and qualitative analyses of the borehole probe data. The lithology of Mushrif Formation was determined by knowing the response of the GR, Spontaneous potential, resistivity, neutron probe, and density, as well as from the analysis of the probe values from the cross plot, as most of the values for this analysis fell in the range of limestone rocks, some of them in the range of dolomite rocks, and a few of them in the range of sandstone.The petro-physical results of the current study showed that Mushrif Formation in the three wells has four distinct units, each of which has petro-physical properties that distinguish it from others. These units were labeled MB2, MB1, CR11, mA, and Mushrif. We used electrical probes, porosity probes, and GR probes to identify the upper (mA) and lower (mB) units. These two units are separated by barrier shales (CR11, Mushrif). mB1 and mB2 are the main reservoir units in the formation, characterized by their high hydrocarbon content and high proportions of mobile hydrocarbons compared to the remaining hydrocarbons. The mB1